VASCULAR PARKINSONISM WITH EARLY COGNITIVE IMPAIRMENT: A CASE REPORT AND LITERATURE REVIEW - Tertia, Clarissa; Trisnawati, Sri Yenni; Widyadharma, I Putu Eka; Samatra, Purwa (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Introduction: Vascular parkinsonism has a prevalence 4.4% to 12% of parkinsonism. Until now there are no specific diagnostic criteria to establish diagnosis of vascular parkinsonism, so it is often misdiagnosed with idiopathic parkinsonism. Case Report: Male, 82 years old, with gait disorder 3 years ago, appeared stiff with small steps. The patient appears to be slower, drooling frequently, and has difficulty swallowing food. The patient was diagnosed with Parkinson's disease and given levodopa/benserazide. However, the progress of the disease was getting worse, so the dose was increased. Since 2 years, patient became forgetful and more irritable. History of ischemic stroke 3 years ago with no sequelae. History of hypertension and gout arthritis (GA). Patient was compos mentis without signs of focal deficit or lateralization, however, there was a cogwheel-type rigidity in all extremities without any tremor. MoCA-Ina (Montreal Cognitive Assesment Indonesian Version) test was 21. The head CT (Computer Tomography) scan revealed chronic lacunar infarct with brain atrophy and small vessel ischemic changes. Then patient was diagnosed with vascular parkinsonism and treated with levodopa, acetosal, candesartan and consulted to medical rehabilitation department. Discussion: Based on criteria of Zijlmans et al., and Winikates and Jankovic, patient is included in vascular parkinsonism, namely the presence of bradykinesia, rigidity and postural instability which indicates a parkinsonism accompanied by 3 vascular scores. Conclusion: Diagnosis of vascular parkinsonism is very complex and challenging. Multidisciplinary management from neurologists and medical rehabilitation specialists must be applied to improve the quality of life, reduce morbidity and mortality.